Pelatihan Literasi Keuangan di SMKN 1 Kota Tangerang - Aldi Samara; Rr Dian Anggraeni; Limajatini Limajatini; Suhendra Suhendra; Juan Barus Gultom (Pusat Riset dan Inovasi Nasional, 2025)
Financial literacy is becoming increasingly important along with the development of the economy, therefore financial literacy is something that cannot be separated from everyday life. For most high school students, it is the first time they manage their own finances without parental supervision. Lack of financial literacy causes mistakes in managing finances. Based on the findings of the Financial Services Authority (OJK) (Wibowo, 2024), the number of bad loans of more than 90 days in the peer-to-peer financial technology (P2P lending) industry, or known as pinjol for the individual category has reached IDR 1.73 trillion as of May 2023. The problem is, the Millennial generation or those aged 19-34 years are the largest